2016
DOI: 10.3389/fncom.2016.00089
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Modeling of Impairment of Evoked Gamma Range Oscillations in Schizophrenia

Abstract: Despite a significant increase in efforts to identify biomarkers and endophenotypic measures of psychiatric illnesses, only a very limited amount of computational models of these markers and measures has been implemented so far. Moreover, existing computational models dealing with biomarkers typically only examine one possible mechanism in isolation, disregarding the possibility that other combinations of model parameters might produce the same network behavior (what has been termed “multifactoriality”). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 68 publications
(111 reference statements)
2
30
0
Order By: Relevance
“…Changes to the GABAergic system have been proposed to explain the reduction in evoked gamma power [32] and modelling work has demonstrated that both, a reduction in GABA levels in schizophrenia patients [89,70] and an increase in decay times at GABAergic synapses [104,70], can lead to reduced ASSR gamma power. On the one hand, a decrease in inhibition due to reduced GABA levels decreases the precise inhibitory control over pyramidal cell firing necessary for a strong gamma rhythm.…”
Section: The Effects Of Variant Combinations Are Comparable To the Efmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to the GABAergic system have been proposed to explain the reduction in evoked gamma power [32] and modelling work has demonstrated that both, a reduction in GABA levels in schizophrenia patients [89,70] and an increase in decay times at GABAergic synapses [104,70], can lead to reduced ASSR gamma power. On the one hand, a decrease in inhibition due to reduced GABA levels decreases the precise inhibitory control over pyramidal cell firing necessary for a strong gamma rhythm.…”
Section: The Effects Of Variant Combinations Are Comparable To the Efmentioning
confidence: 99%
“…Furthermore, optogenetically driving PV + interneurons was found to enhance gamma rhythms [11]. Consequently, cellular level alterations at PV + interneurons in schizophrenia have been linked to well-known auditory steady-state response (ASSR) deficits in the gamma band [104,70,71,47,86]. However, these studies have focused on changes to the strength and temporal dynamics of synaptic transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The first model is based on a biophysically detailed model of primary auditory cortex by Beeman [3]. It has recently been used to study ASSR deficits by our group [30]. The model was implemented using the neural simulator GEN-ESIS [4,5].…”
Section: Models Capabilities Tests and Morementioning
confidence: 99%
“…We do not discuss the models in more detail here, since they have been described elsewhere [3,30,58,29]. Furthermore, our focus lies on the framework with which to use, validate and compare models not on the models themselves.…”
Section: Models Capabilities Tests and Morementioning
confidence: 99%
See 1 more Smart Citation